2014
DOI: 10.7314/apjcp.2014.15.20.8563
|View full text |Cite
|
Sign up to set email alerts
|

Self-Collection Tools for Routine Cervical Cancer Screening: A Review

Abstract: Sub-optimal participation is a major problem with cervical cancer screening in developing countries which have no organized national screening program. There are various notable factors such as 'embarrassment', 'discomfort' and 'no time' cited by women as they are often also the bread winners for the family. Implementation of self-sampling methods may increase their participation. The aim of this article was to provide a survey of various types of self-sampling tools which are commonly used in collection of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Unlike plasma, CVF does not contact many other tissues, and its volume is limited (milliliters versus liters). Moreover, the liquid can easily be collected by self-sampling in a non-invasive way using devices for lavages [ 36 , 66 ], or using tampons [ 38 , 67 ] (self-sampling devices developed before 2014 were reviewed in Othman et al [ 68 ]). Therefore, self-sampling of CVF could overcome the practical (e.g., busy schedule, transport, and distance), emotional (e.g., fear of pain and embarrassment), and cognitive (e.g., low perceived risk and absence of symptoms) barriers that some women experience in attending cervical cancer screening programs [ 69 71 ].…”
Section: Cervical Cancer and The Need For A Bedside Assaymentioning
confidence: 99%
“…Unlike plasma, CVF does not contact many other tissues, and its volume is limited (milliliters versus liters). Moreover, the liquid can easily be collected by self-sampling in a non-invasive way using devices for lavages [ 36 , 66 ], or using tampons [ 38 , 67 ] (self-sampling devices developed before 2014 were reviewed in Othman et al [ 68 ]). Therefore, self-sampling of CVF could overcome the practical (e.g., busy schedule, transport, and distance), emotional (e.g., fear of pain and embarrassment), and cognitive (e.g., low perceived risk and absence of symptoms) barriers that some women experience in attending cervical cancer screening programs [ 69 71 ].…”
Section: Cervical Cancer and The Need For A Bedside Assaymentioning
confidence: 99%
“…According to these reasons, cervical cancer remains as a serious health problem in the world. In developing countries, which do not have screening programs, cervical cancer is one of the obvious causes of mortality (Othman et al, 2014). However, this cancer is known as a preventable cancer because it has one long pre-invasion step and available cytology screening programs (Monsonego et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It was previously shown that self-sampling using the Fournier-sampler on 292 subjects was not clinically acceptable due to lower sensitivity (41%) in sampling collection compared with conventional physician-obtained sampling (Aziz et al, 2013). It was previously shown that different methods of self-sampling obtain various amounts of cell mixture comprising more vaginal cells and less endocervical cells (Othman and Zaki, 2014). Another reason that might contribute to the difference in sample collection between self-sampling technique and physician-obtained sampling methods might be due to the existence of postmenopausal subjects.…”
Section: Discussionmentioning
confidence: 99%